Autosomal dominant optic atrophy associated with hearing impairment and impaired glucose regulation caused by a missense mutation in the WFS1 gene. Issue 5 (28th April 2006) - Eiberg, H; Hansen, L; Kjer, B; Hansen, T; Pedersen, O; Bille, M; Rosenberg, T; Tranebjærg, L
Abstract : Autosomal dominant optic atrophy (ADOA) is genetically heterogeneous, with OPA1 on 3q28 being the most prevalently mutated gene. Additional loci are OPA3, OPA4, and OPA5, located at 19q13.2, 18q12.2, and 22q12.1–q13.1, respectively. Mutations in the WFS1 gene, at 4p16.3, are associated with either optic atrophy (OA) as part of the autosomal recessive Wolfram syndrome or with autosomal dominant progressive low frequency sensorineural hearing loss (LFSNHL) without any ophthalmological abnormalities. Linkage and sequence mutation analyses of the ADOA candidate genes OPA1, OPA3, OPA4, and OPA5, including the genes WFS1, GJB2, and GJB6 associated with recessive inherited OA or dominant LFSNHL, were performed. We identified one novel WFS1 missense mutation E864K, c.2590G→A in exon 8 that co-segregates with ADOA combined with hearing impairment and impaired glucose regulation. This is the first example of autosomal dominant optic atrophy and hearing loss associated with a WFS1 mutation, supporting the notion that mutations in WFS1 as well as in OPA1 may lead to ADOA combined with impaired hearing.